Managing market instability Analysing Dynamic capabilities in a Medium-sized Construction Company - Bengtsson, Buster; Johansson, Jonathan (My University, 2024)
This research examines how a medium-sized construction company in Gothenburg navigates market instability. Employing a qualitative interview study, the research explores Company X’s adaptive strategies across various project stages: project selection, tendering process, planning phase, and production. Emphasis is placed on the dynamic capabilities framework to address market challenges and opportunities. The findings underscore the significance of strategic project selection, precise cost calculations, stakeholder collaboration, and early involvement of production staff in maintaining competitiveness. Despite heightened competition and volatile material costs, focusing on public sector projects such as schools and hospitals has proven effective. This study concludes that for construction companies to survive and thrive in unstable markets, they must develop and implement strategies that enhance flexibility and promote continuous improvement. The insights provided can guide similar firms in developing dynamic capabilities and sustain a competitive edge.
Keywords: Dynamic capabilities; Market instability; Construction sector; Competitiveness